2020
DOI: 10.1371/journal.pone.0240323
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and factors associated with Trichomonas vaginalis infection in indigenous Brazilian women

Abstract: There is a scarcity of studies on the prevalence of Trichomonas vaginalis (TV) in indigenous populations of Brazil. We conducted a cross-sectional study between January and December 2018, on indigenous women living nearby an urban center of the Midwest region of Brazil and determined the prevalence of TV. Factors associated with TV infection and a comparison of molecular and direct microscopy diagnoses were determined. 241 indigenous women aged above 18 years participated in the study. Cervical and vaginal bru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 24 publications
1
5
1
Order By: Relevance
“…Our reported TV prevalence was higher than that reported in Poland (0%), 15 France (1.7%), 16 China (1.64%) 17 and the USA (3.1%), 18 while it was lower than the frequency rates reported in Turkey (6.17%), 19 Brazil (27.8%), 20 Ethiopia (9.62%) 21 and Papua New Guinea (39.3%). 22 Obviously, the higher rates and increased risk of TV in some countries and poor nations may be related to poverty, a low level of education, a lack of knowledge regarding safe sex (e.g.…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…Our reported TV prevalence was higher than that reported in Poland (0%), 15 France (1.7%), 16 China (1.64%) 17 and the USA (3.1%), 18 while it was lower than the frequency rates reported in Turkey (6.17%), 19 Brazil (27.8%), 20 Ethiopia (9.62%) 21 and Papua New Guinea (39.3%). 22 Obviously, the higher rates and increased risk of TV in some countries and poor nations may be related to poverty, a low level of education, a lack of knowledge regarding safe sex (e.g.…”
Section: Discussioncontrasting
confidence: 78%
“…Across different studies from a worldwide perspective, condom use was not found to be significantly associated with TV infection. 20 , 28 , 39 , 40 In a Sudanese study, the other two variables were also not significantly associated with a history of abortion and/or being pregnant. 26 LBW and PTD are two major issues regarding TV infection during gestation 41 ; although these parameters were not considered in Iranian studies, further investigations are required to obtain a more accurate picture of the association between pregnancy and TV infection sequelae in pregnant women in Iran.…”
Section: Discussionmentioning
confidence: 83%
“…Using a condom for sex was a protective factor against T. vaginalis infection, as Barbosa et al found (Barbosa et al 2020). In this study, women who did not use condoms for sex were twice as likely to be T. vaginalis positive as women who did.…”
Section: Discussionsupporting
confidence: 48%
“…(2020) and Fernando et al . (2012) [ 46 , 53 ]. The present study reported a statistically significant relationship between Trichomonas infection and multiple sexual partners ( p = 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent study carried out by Barbosa et al . (2020) [ 53 ] showed a high prevalence of Trichomonas infection among sex workers. The present study observed an increased incidence of infection among commercial sex workers, even though the findings were not statistically significant.…”
Section: Discussionmentioning
confidence: 99%